504. LONG-TERM PROGNOSIS AND CAUSES OF DEATH IN CLINICAL STAGE I ESOPHAGEAL CANCER PATIENTS AFTER ESOPHAGECTOMY. (24th September 2022) - Niihara, Masahiro; Yamashita, Keishi; Higuchi, Tadashi; Chuman, Motohiro; Washio, Marie; Sakuraya, Mikiko; Hiki, Naoki
Abstract: For patients with clinical stage (cStage) I esophageal cancer that were not indicated for endoscopic resection, esophagectomy was the standard treatment if surgery was desired. The long-term prognosis after surgical resection of cStage I esophageal cancer was 86.5% of the 5-year survival rate in the results of the JCOG0502 study. The aim of this study was to review the long-term survival the causes of death in cStage I esophageal cancer patients after esophagectomy. Between January 2004 to February 2021, 138 patients underwent radical esophagectomy for the treatment of cStage I esophageal cancer in our institution. These cases also included non-curative resection cases after endoscopic resection. The patient cohort contained 116 (84 %) males, and 22 (16 %) patients. The median age was 68.5 years (range, 49–82). We estimated long-term overall and cancer-specific cumulative mortality for these patients. In addition, we analyzed the deaths from other causes. The median follow-up period was 52 months. The 5-year survival rates and cancer-specific survival rate were 82.8% and 87.3%, respectively. There were two surgery-related deaths. Other-cause deaths were observed in 19 patients. The causes were other cancers in 7 patients, respiratory diseases (pneumonia, acute exacerbation of COPD) in 4 patients, heart failure in 1 patient, and unknown in 7 patients. The breakdown of other cancers was cervical esophageal cancer in 1 patient, hypopharyngeal cancer in 3 patients, lung cancer in 2 patients, and malignant lymphoma in 1 patient. Of the 4 patients who were caused by respiratory disease, 3 had recurrent laryngeal nerve palsy as postoperative complication. The long-term prognosis of cStage I esophageal cancer patients after esophagectomy in our institution was comparable to that of other clinical trials. Head and neck cancer and lung cancer accounted for the majority of deaths due to other causes. In addition, most of the cases caused by respiratory disease had postoperative recurrent laryngeal nerve palsy. It was considered that attention should be paid to aspiration even during outpatient follow-up.